Risk Assessment Approach to Regulatory Compliance Challenges in Aging Facilities: A Case Study of Harlypet Oil and Gas Nigeria Limited Facilities (Nigerian Journal of Technology, 2021)
Compliance with new regulations in old plants remains a recurring challenge because of negative outcome of incidents. This challenge stems from uncertainties in the facilities’ integrity, owing to inadequacy of existing integrity-validating technologies. Process facilities deteriorate through cyclic operations, while encroachments from expanding population characteristically raise the risk-levels, leading to need for higher grade materials to meet operational expansions. Retroactive compliance becomes a nightmare with every new regulation without a robust cost-to-benefit assurance. This paper discusses two-phased qualitative and quantitative risk modelling approach through systematic field-data-gathering, hazards identification and analysis by a twelve-man risk management engineers. The methodology successfully computed a ``health-check" of the facility's compliance to new regulations, 17 high-risk-hazards were extracted from 42 potential hazards and successfully established varied individual risk levels ranging from 4.07E-06 to 1.64E-04/year. Also, risks ranged from 1.00E-04 to 5.00E-05/year of tolerable risks to the environment, society, and business were recorded across the facility while, 22 risk-mitigation actions were recommended.http://dx.doi.org/10.4314/njt.v40i2.6